FAKTOR PENENTU MOTIVASI DAN INTENSI BERWIRAUSAHA MAHASISWA - Miftachul Ma’arif (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2022)
The purpose of this study was to determine the effect of creativity and self-efficacy on student entrepreneurship motivation; knowing the effect of creativity and self-efficacy on the entrepreneurial intention of students and knowing the effect of motivation on the entrepreneurial intention of students. The method of data collection was obtained by using a questionnaire on students in the city of Yogyakarta and Surakarta, then 216 respondents were collected. The data analysis tool used is the AMOS Structural Equation Modeling (SEM) technique. The results showed that there was an influence between creativity and self-efficacy on students' entrepreneurial motivation; there is an influence between creativity on students' entrepreneurial intentions and there is an influence of motivation on students' entrepreneurial intentions. However, self-efficacy does not affect the entrepreneurial intention of students